Warming may extend tree growing seasons and compensate for reduced carbon uptake during dry periods. (8th May 2022) - Grossiord, Charlotte; Bachofen, Christoph; Gisler, Jonas; Mas, Eugénie; Vitasse, Yann; Didion‐Gency, Margaux
Abstract: Warming and drought alter plant phenology, photosynthesis and growth with important consequences for the global carbon cycle and the earth's climate. Yet, few studies have attempted to tease apart their effects on tree phenology, particularly leaf senescence, and on source and sink activity. We experimentally assessed the single and combined effects of warming and reduced soil moisture on the phenology (leaf‐out and senescence date, growing season length) and above‐ground sink (height and diameter growth, leaf area and Huber values) and source activity (net photosynthesis, photosynthetic efficiency, chlorophyll concentration and total carbon [C] uptake) of two tree species with distinct strategies to deal with drought: European beech and pubescent oak. Warming advanced leaf‐out, irrespective of soil moisture levels, particularly in oak and to a lower extent in beech, leading to a prolonged growing season in oak but not beech. No impacts of warming on senescence timing were found for both species. Reduced moisture had little impact on the phenology of both species. Warming‐induced advances in phenology and higher photosynthetic efficiency increased the annual C uptake for oak and compensated for the reduced photosynthetic activity in the presence of reduced moisture. Conversely, for beech, source activity, including yearly C uptake, was lower in all treatments than the control, indicating no compensation of the C budget by phenological shifts. Synthesis . Our results demonstrate that a warming‐driven earlier activity and higher photosynthetic efficiency compensates for reduced photosynthesis during hot and dry periods, but only for pubescent oak, which is a rather drought‐tolerant species. Current predictions of warming‐induced mitigation effects through extended C uptake seem incorrect for beech. Abstract : Our results demonstrate that a warming‐driven earlier activity and higher photosynthetic efficiency compensates for reduced photosynthesis during hot and dry periods, but only for pubescent oak, which is a rather drought‐tolerant species. Current predictions of warming‐induced mitigation effects through extended C uptake seem incorrect for beech.